Development and Evaluation of the Cotton Leaf Curl Kokhran Virus-Burewala Bidirectional Promoter for Enhanced Cry1Ac Endotoxin Expression in Bt Transgenic Cotton - Muhammad Aleem Ashraf; Ahmad Ali Shahid; Abdul Qayyum Rao; Judith K. Brown; Tayyab Husnain (Applied Sciences, 2022)
Fluctuation in Cry1Ac endotoxin levels expressed in transgenic Bacillus thuringiensis (Bt) cotton (Gossypium hirsutum L.) can result in a variation in efficacy throughout the growing season. Here, a green tissue-specific strong promoter of the cotton leaf curl Kokhran virus-Burewala (CLCuKoV-Bu) C1 gene is reported that can direct consistently high levels of Cry1Ac endotoxin expression in transformed cotton plants. The objective of this study was to investigate the capacities of the CLCuKoV-BuC1 promoter to drive transcription of Cry1Ac and stably express endotoxin in mature leaves and bolls of transgenic cotton plants, compared to the traditional CaMV35S promoter. The Cry1Ac gene expression cassettes were constructed under the control of a bidirectional promoter and transformed into cotton ‘MNK-786′. The expression of Cry1Ac constructs was evaluated in transient and stable expression systems using Nicotiana tabacum ‘Rustica’ and cotton plants, respectively. Accumulation of the Cry1Ac expressed in two resultant transgenic cotton plants harboring the constructs driven by the CLCuKoV-BuC1 and CaMV35S promoter, respectively, was analyzed using a commercially available enzyme-linked immunosorbent assay. In leaves and bolls of two cotton plants shown to express CLCuKoV-BuC1-Cry1Ac (CLCuV-Ac), the Cry1Ac protein accumulated at 400 and 300 ng g−1 per fresh tissue weight, respectively, whereas no toxin was detectable in the roots. In contrast, CaMV35S-Cry1Ac transgenic cotton plants accumulated three times less Cry1Ac protein than those transformed with CLCuV-Ac. Results indicate that the greatest amount of Cry1Ac endotoxin accumulated in transgenic cotton when expression was driven by the CLCuKoV-BuC1 compared to the CaMV35S promoter. Thus, the CLCuKoV-BuC1 promoter offered more robust transgene expression in cotton plants than the traditional CaMV35S promoter. The newly validated CLCuV-Ac promoter of begomoviral origin offers an exciting alternative as a robust promoter for genetic engineering of cotton and other plants.